Pole piece and preparation method thereof, positive electrode slurry, lithium ion battery and electric device

By using a electrode sheet with characteristic lithium iron phosphate material in the positive electrode of lithium ion batteries, the problem of insufficient charging performance of lithium ion batteries under low temperature conditions is solved, and more efficient low-temperature cycling performance and the effect of reducing system complexity and cost is achieved.

CN119852327AActive Publication Date: 2025-04-18JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510050437.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Lithium-ion batteries have poor charging performance under low temperature conditions, and existing solutions increase the complexity and cost of the battery system, and self-heating consumes battery energy.

Method used

Using an electrode sheet including lithium iron phosphate material, a suitable active layer is formed for the positive electrode of lithium ion battery by controlling the specific relationship between D50 and tap density of lithium iron phosphate material and the specific relationship between D90 and D10.

Benefits of technology

It effectively improves the low-temperature charging performance and low-temperature circulation performance of lithium-ion batteries, reduces dependence on self-heating systems, and reduces system complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852327A_ABST
    Figure CN119852327A_ABST
Patent Text Reader

Abstract

The invention relates to a pole piece and a preparation method thereof, positive electrode slurry, a lithium ion battery and an electric device. The pole piece comprises a current collector and an active layer arranged on at least one side of the current collector, the active layer comprises a lithium iron phosphate material, the D50 of the lithium iron phosphate material is beta [mu] m, the tap density of the lithium iron phosphate material is gamma g / m < 3 >, a is equal to beta / gamma, a is more than or equal to 0.7 and less than or equal to 1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, and b is more than or equal to 4 and less than or equal to 8. By controlling the specific relationship between the D50 and the tap density of the lithium iron phosphate material and the specific relationship between the D90 and the D10 of the lithium iron phosphate material, the lithium iron phosphate material is applied to the lithium ion battery, and the low-temperature charging performance and the low-temperature cycle performance of the lithium ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to a pole piece and a preparation method thereof, a positive electrode slurry, a lithium-ion battery and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in mobile phones, tablets, notebooks, electric vehicles, and energy storage. At present, the best operating temperature range for lithium-ion batteries is at room temperature (25°C), and their charging performance is poor under low temperature conditions. The current solution is to add a heating system and a temperature control system to the lithium-ion battery system. Under low temperature conditions, the battery system self-heats and allows the battery cells to operate in a suitable temperature range. However, adding a heating system and a temperature control system to the lithium-ion battery system will increase the complexity of the battery system, reduce the reliability of the system, increase the cost of the battery system, and the self-heating of the system will also consume the energy of the battery system itself. Therefore, the low temperature performance of the battery needs to be improved. Summary of the invention

[0003] Based on this, the present application provides a pole piece with good low-temperature performance and a preparation method thereof, a positive electrode slurry, a lithium-ion battery and an electrical device.

[0004] The technical solution of this application to solve the above technical problems is as follows.

[0005] The present application provides a pole piece, comprising a current collector and an active layer disposed on at least one side of the current collector, wherein the active layer comprises a lithium iron phosphate material, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

[0006] In some embodiments, in the pole piece, the specific surface area of ​​the lithium iron phosphate material is δ m 2 / g, c=β / δ, 0.03≤c≤0.09.

[0007] In some of the embodiments, in the pole piece, 0.25 μm≤D10≤0.55 μm.

[0008] In some of the embodiments, in the pole piece, 0.5 μm≤D50≤1.1 μm.

[0009] In some of the embodiments, in the pole piece, 1.6 μm≤D90≤4 μm.

[0010] In some of the embodiments, in the pole piece, 4.5 μm≤D99≤8.5 μm.

[0011] In some embodiments, in the pole piece, the tap density of the lithium iron phosphate material is 0.5 g / m 3 ~1.5 g / m 3 .

[0012] In some embodiments, in the pole piece, the specific surface area of ​​the lithium iron phosphate material is 6 m 2 / g ~30 m 2 / g.

[0013] On one hand, the present application provides a method for preparing a pole piece, comprising the following steps:

[0014] An active layer is disposed on at least one side of the current collector, wherein the active layer comprises a lithium iron phosphate material, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

[0015] The present application provides a slurry including a lithium iron phosphate material, a first binder and a first conductive agent, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

[0016] In some embodiments, the slurry satisfies at least one of the following characteristics:

[0017] (1) The first binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and sodium polyacrylate;

[0018] (2) the first conductive agent comprises at least one of carbon black, acetylene black, ketjen carbon, carbon nanotubes and carbon nanofibers;

[0019] (3) The mass ratio of the lithium iron phosphate material, the first binder and the first conductive agent is 95-98:1-3:1-3.

[0020] On one hand, the present application provides a lithium-ion battery, including the above-mentioned pole piece or the pole piece prepared by the above-mentioned pole piece preparation method.

[0021] In some embodiments, in a lithium ion battery, the lithium ion battery comprises a positive electrode and a negative electrode, the electrode sheet serves as the positive electrode, the negative electrode comprises a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, the negative electrode active layer comprises graphite, the D50 of the graphite is σ μm, and the specific surface area of ​​the graphite is ω m 2 / g, d=σ / ω, 2.5≤d≤7.5. .

[0022] In some embodiments, in lithium-ion batteries, the tap density of the graphite is θ g / m 3 , e=σ / θ, 3≤e≤9.

[0023] In some of the embodiments, in the lithium-ion battery, the ratio of D90 of the graphite to D10 of the graphite is f, 2≤f≤6.

[0024] In some embodiments, in the lithium-ion battery, the graphite satisfies at least one of the following characteristics:

[0025] (1) 2 μm ≤ D10 ≤ 6 μm;

[0026] (2) 4 μm≤D50≤12 μm;

[0027] (3)9 μm≤D90≤16 μm;

[0028] (4) 14 μm≤D99≤26 μm;

[0029] (5) The tap density of the graphite is 0.8 g / m 3 ~2 g / m 3 ;

[0030] (6) The specific surface area of ​​the graphite is 0.8 m 2 / g ~3 m 2 / g.

[0031] On one hand, the present application provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0032] Compared with the prior art, the positive electrode slurry of the present application has the following beneficial effects:

[0033] The pole piece of the present application includes lithium iron phosphate material. By controlling the specific relationship between D50 and tap density of the lithium iron phosphate material, and controlling the specific relationship between D90 and D10 of the lithium iron phosphate material, it is applied to lithium-ion batteries, which can effectively improve the low-temperature charging performance and low-temperature cycling performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 It is a comparison chart of the low temperature cycle of the battery cells prepared in Example 1 and Comparative Example 1 at 5°C 0.5P / 0.5P 100%DOD;

[0036] Figure 2 This is a diagram showing the negative electrode surface of the battery cell prepared in Example 1 after 0.2P charging at -10°C low temperature;

[0037] Figure 3 This is a diagram of the negative electrode surface of the battery cell prepared in Comparative Example 1 after 0.2P charging at -10°C low temperature conditions. DETAILED DESCRIPTION

[0038] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0039] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0041] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0042] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0043] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0044] D50: median particle size, the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%, that is, the diameter of the particle when the particle mass in the particle group is divided into half. Its physical meaning is that the mass of particles larger than its particle size accounts for 50%, and the mass of particles smaller than its particle size also accounts for 50%.

[0045] D10: The particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 10%. Its physical meaning is that the particle mass smaller than it accounts for 10%.

[0046] D90: The particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 90%. Its physical meaning is that the mass of particles smaller than it accounts for 90%.

[0047] D99: The particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 99%. Its physical meaning is that the mass of particles smaller than it accounts for 99%.

[0048] An embodiment of the present application provides a pole piece, including a current collector and an active layer disposed on at least one side of the current collector, wherein the active layer includes a lithium iron phosphate material, the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of lithium iron phosphate material to D10 of lithium iron phosphate material is b, 4≤b≤8.

[0049] The pole piece of the present application includes lithium iron phosphate material. By controlling the specific relationship between D50 and tap density of the lithium iron phosphate material, and controlling the specific relationship between D90 and D10 of the lithium iron phosphate material, it is applied to lithium-ion batteries, which can effectively improve the low-temperature charging performance and low-temperature cycling performance of the lithium-ion battery.

[0050] It can be understood that the active layer can be provided on one side or both sides of the current collector.

[0051] It can be further understood that a includes but is not limited to 0.7, 0.8, 0.9, 1, 1.1, and 1.2; b includes but is not limited to 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, and 8; in some examples, any two of these point values ​​can be within the range formed by the end values, the same below.

[0052] Optionally, 0.7≤a≤1.1.

[0053] Optionally, 5≤b≤7.

[0054] In some of these examples, the specific surface area of ​​the lithium iron phosphate material in the electrode is δ m 2 / g, c=β / δ, 0.03≤c≤0.09.

[0055] It will be appreciated that c includes but is not limited to 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, and 0.09.

[0056] Optionally, 0.05≤c≤0.07.

[0057] On the basis of controlling the relationship between D50 and tap density, and between D90 and D10 of lithium iron phosphate materials, further controlling the relationship between particle size D50 and specific surface area of ​​lithium iron phosphate materials can further improve the low-temperature charging performance and low-temperature cycling performance of lithium-ion batteries.

[0058] In some of these examples, in the pole piece, 0.25 μm ≤ D10 ≤ 0.55 μm.

[0059] It can be understood that D10 of the lithium iron phosphate material includes but is not limited to 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, and 0.55 μm.

[0060] Optionally, 0.3 μm≤D10≤0.45 μm.

[0061] In some of these examples, in the pole piece, 0.5 μm ≤ D50 ≤ 1.1 μm.

[0062] It can be understood that the D50 of the lithium iron phosphate material includes but is not limited to 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, and 1.1 μm.

[0063] Optionally, 0.7 μm≤D50≤0.9 μm.

[0064] In some of these examples, in the pole piece, 1.6 μm ≤ D90 ≤ 4 μm.

[0065] It can be understood that the D90 of the lithium iron phosphate material includes but is not limited to 1.6 μm, 1.8 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, and 4 μm.

[0066] Optionally, 1.8 μm≤D90≤3.5 μm.

[0067] In some of these examples, in the pole piece, 4.5 μm ≤ D99 ≤ 8.5 μm.

[0068] It can be understood that D99 of lithium iron phosphate materials includes but is not limited to 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, and 8.5 μm.

[0069] Optionally, 5.5 μm≤D99≤7.5 μm.

[0070] In some of these examples, the tap density of the lithium iron phosphate material in the pole piece is 0.5 g / m 3 ~1.5 g / m 3 .

[0071] It is understood that the tap density of lithium iron phosphate materials includes but is not limited to 0.5 g / m 3 , 0.6 g / m 3 , 0.75 g / m 3, 0.8 g / m 3 , 1 g / m 3 , 1.1 g / m 3 , 1.2 g / m 3 , 1.3 g / m 3 , 1.4 g / m 3 , 1.5 g / m 3 .

[0072] In some of these examples, the specific surface area of ​​the lithium iron phosphate material in the electrode is 6 m 2 / g ~36 m 2 / g.

[0073] It is understood that the specific surface area of ​​lithium iron phosphate materials includes but is not limited to 6 m 2 / g, 8 m 2 / g, 10 m 2 / g, 12m 2 / g, 14.5 m 2 / g, 16 m 2 / g, 20 m 2 / g, 25 m 2 / g, 30 m 2 / g, 32 m 2 / g, 36 m 2 / g.

[0074] On the basis of controlling the relationship between D50 and tap density, D90 and D10, and particle size D50 and specific surface area of ​​lithium iron phosphate materials, further controlling the range of particle size D10, D50, D90, D99, etc. of lithium iron phosphate materials can further improve the low-temperature charging performance and low-temperature cycling performance of lithium-ion batteries.

[0075] An embodiment of the present application provides a slurry including a lithium iron phosphate material, a first binder and a first conductive agent, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of lithium iron phosphate material to D10 of lithium iron phosphate material is b, 4≤b≤8.

[0076] In some examples, in the slurry, the first binder includes at least one of polyvinylidene fluoride, styrene butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and sodium polyacrylate.

[0077] In some examples, in the slurry, the first conductive agent includes at least one of carbon black, acetylene black, Ketjen carbon, carbon nanotubes, and carbon nanofibers.

[0078] It can be understood that the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0079] In some of the examples, in the slurry, the mass ratio of the lithium iron phosphate material, the first binder, and the first conductive agent is 95-98:1-3:1-3.

[0080] It can be understood that in the slurry, the mass ratio of lithium iron phosphate material to the first binder is 95~98:1~3; the mass ratio of lithium iron phosphate material to the first conductive agent is 95~98:1~3; the mass ratio of the first binder to the first conductive agent is 1~3:1~3. Furthermore, the mass ratio of the lithium iron phosphate material to the first binder includes but is not limited to 95:1, 96:1, 97:1, 98:1, 95:2, 96:2, 97:2, 98:2, 95:3, 96:3, 97:3, 98:3; the mass ratio of the lithium iron phosphate material to the first conductive agent includes but is not limited to 95:1, 96:1, 97:1, 98:1, 95:2, 96:2, 97:2, 98:2, 95:3, 96:3, 97:3, 98:3; the mass ratio of the first binder to the first conductive agent includes but is not limited to 1:1, 1:2, 1:3, 2:1, 2:3, 3:1, 3:2.

[0081] The slurry provided in the present application combines the above-mentioned specific lithium iron phosphate material, the first binder and the first conductive agent in a specific ratio, and is used to form an active layer of a pole piece, which can greatly improve the low-temperature charging performance and low-temperature cycle performance of a lithium-ion battery.

[0082] An embodiment of the present application provides a method for preparing a slurry, comprising the following steps:

[0083] The lithium iron phosphate material, the first binder and the first conductive agent are mixed to prepare a slurry; the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of lithium iron phosphate material to D10 of lithium iron phosphate material is b, 4≤b≤8.

[0084] It can be understood that the method for preparing the slurry provided in the present application can prepare the above-mentioned slurry, and the above-mentioned slurry can be prepared by the method for preparing the slurry provided in the present application; that is, the method for preparing the slurry provided in the present application and the characteristics of the slurry provided above are mutually applicable.

[0085] An embodiment of the present application provides a method for preparing a pole piece, comprising the following steps:

[0086] An active layer is disposed on at least one side of the current collector, wherein the active layer comprises a lithium iron phosphate material, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of lithium iron phosphate material to D10 of lithium iron phosphate material is b, 4≤b≤8.

[0087] It can be understood that the method for preparing the pole piece provided in the present application can produce the above-mentioned pole piece, the above-mentioned pole piece can be produced by the method for preparing the pole piece provided in the present application, and the characteristics of the above-mentioned pole piece and the method for preparing the pole piece provided in the present application can be mutually applicable.

[0088] In some of the examples, the method for preparing the pole piece includes the following steps:

[0089] The slurry or the slurry prepared by the slurry preparation method is placed on at least one side of the current collector, and is solidified to form an active layer on at least one side of the current collector.

[0090] It is understood that the present application does not limit the type of current collector, and conventional materials in the art can be used. For example, when the electrode is a positive electrode, the current collector is a positive electrode current collector; further, the positive electrode current collector includes but is not limited to aluminum foil.

[0091] An embodiment of the present application provides a lithium-ion battery, including a pole piece or a pole piece made by the above-mentioned pole piece preparation method.

[0092] The lithium-ion battery provided in the present application, including the above-mentioned pole piece or the pole piece prepared by the above-mentioned pole piece preparation method, can give the lithium-ion battery better low-temperature charging performance and low-temperature cycle performance.

[0093] In some of the examples, in a lithium-ion battery, the lithium-ion battery includes a positive electrode and a negative electrode, the electrode sheet serves as the positive electrode, and the negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector.

[0094] It can be understood that when the above-mentioned pole piece is used as a positive electrode, the current collector in the pole piece is a positive electrode current collector, and the active layer in the pole piece is a positive electrode active layer.

[0095] In some of these examples, in lithium-ion batteries, the D50 of graphite is σ μm and the specific surface area of ​​graphite is ω m 2 / g, d=σ / ω, 2.5≤d≤7.5.

[0096] It will be understood that d includes but is not limited to 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, and 7.5.

[0097] Optionally, 3≤d≤5.

[0098] In some of these examples, the tap density of graphite in lithium-ion batteries is θ g / m 3 , e=σ / θ, 3≤e≤9.

[0099] It will be understood that e includes but is not limited to 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, and 9.

[0100] Optionally, 3≤e≤7.

[0101] In some of these examples, in lithium-ion batteries, the ratio of D90 of graphite to D10 of graphite is f, 2≤f≤6.

[0102] It will be understood that f includes but is not limited to 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, and 6.

[0103] Optionally, 3≤f≤4.

[0104] In some of these examples, in lithium-ion batteries, 2 μm ≤ D10 ≤ 6 μm.

[0105] It can be understood that D10 of graphite includes but is not limited to 2 μm, 3 μm, 4 μm, 5 μm, and 6 μm.

[0106] In some of these examples, in lithium-ion batteries, 4 μm ≤ D50 ≤ 12 μm.

[0107] It can be understood that D50 of graphite includes but is not limited to 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, and 12 μm.

[0108] In some of these examples, in lithium-ion batteries, 9 μm ≤ D90 ≤ 16 μm.

[0109] It can be understood that D90 of graphite includes but is not limited to 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, and 16 μm.

[0110] In some of these examples, in lithium-ion batteries, 14 μm ≤ D99 ≤ 26 μm.

[0111] It will be appreciated that D99 of graphite includes, but is not limited to, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, and 26 μm.

[0112] In some of these examples, graphite in lithium-ion batteries has a tap density of 0.5 g / m 3 ~4 g / m 3 .

[0113] It is understood that the tap density of graphite includes but is not limited to 0.5 g / m3 , 0.6 g / m 3 , 0.8 g / m 3 , 1 g / m 3 , 1.2 g / m 3 , 1.32 g / m 3 , 1.5 g / m 3 , 2 g / m 3 , 2.5 g / m 3 , 3 g / m 3 3.5 g / m 3 , 4 g / m 3 .

[0114] In some examples, the specific surface area of ​​graphite in lithium-ion batteries is 0.8 m 2 / g ~3 m 2 / g.

[0115] It is understood that the specific surface area of ​​graphite includes but is not limited to 0.8 m 2 / g, 1 m 2 / g, 1.28 m 2 / g, 1.5 m 2 / g, 2 m 2 / g, 2.5 m 2 / g, 3 m 2 / g.

[0116] In some of these examples, in lithium-ion batteries, the preparation of the negative electrode includes the following steps:

[0117] The negative electrode slurry is disposed on at least one side of the negative electrode current collector and solidified to form a negative electrode active layer on at least one side of the negative electrode current collector.

[0118] Furthermore, the negative electrode slurry includes graphite, a second binder and a second conductive agent.

[0119] In some of the examples, in the lithium-ion battery, the second binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and sodium polyacrylate.

[0120] In some of the examples, in the lithium-ion battery, the second conductive agent includes at least one of carbon black, acetylene black, Ketjen carbon, carbon nanotubes, and carbon nanofibers.

[0121] It can be understood that the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0122] In some of the examples, in the lithium-ion battery, the mass ratio of graphite, the second binder, and the second conductive agent is 94-98:1-3:1-3.

[0123] It can be understood that in the lithium-ion battery, the mass ratio of graphite to the second binder is 94~98:1~3; the mass ratio of graphite to the second conductive agent is 94~98:1~3; the mass ratio of the second binder to the second conductive agent is 1~3:1~3. Furthermore, the mass ratio of graphite to the second binder includes but is not limited to 94:1, 95:1, 96:1, 97:1, 98:1, 94:2, 95:2, 96:2, 97:2, 98:2, 94:3, 95:3, 96:3, 97:3, 98:3; the mass ratio of graphite to the second conductive agent includes but is not limited to 94:1, 95:1, 96:1, 97:1, 98:1, 94:2, 95:2, 96:2, 97:2, 98:2, 94:3, 95:3, 96:3, 97:3, 98:3; the mass ratio of the second binder to the second conductive agent includes but is not limited to 1:1, 1:2, 1:3, 2:1, 2:3, 3:1, 3:2.

[0124] It can be understood that in some of the examples, the active layer of the above-mentioned pole piece (positive electrode and / or negative electrode) can be directly arranged on one side of at least one surface of the current collector; in other examples, other coatings can be arranged on one side of at least one surface before the active layer is arranged; some coatings can also be arranged on the active layer, such as at least one of a functional coating and a protective film coating, etc.; further, the functional coating can include a carbon material coating (including at least one of single-walled conductive carbon tubes, multi-walled conductive carbon tubes, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, soft carbon and hard carbon, etc.) and a lithium-philic / sodium-philic metal composite coating, etc.; the protective film coating includes but is not limited to at least one of an organic polymer coating, an inorganic compound coating and a polymer / inorganic composite material coating, etc.; further, the organic polymer coating includes but is not limited to at least one of a polyethylene terephthalate (PET) coating, a polypropylene (PP) coating, a polyethylene PE coating, a polyvinylidene fluoride (PVDF) coating, an ethylene-vinyl acetate polymer (EVA) coating, etc.

[0125] The lithium-ion battery provided in the present application can be used in, but is not limited to, electrical devices such as vehicles, ships or aircraft.

[0126] An embodiment of the present application provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0127] Furthermore, the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0128] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0129] Example 1

[0130] Lithium iron phosphate positive electrode material: particle size D10 is 0.39 μm, D50 is 0.82 μm, D90 is 2.01 μm, D99 is 6.31 μm, and specific surface area S is 14.50 m 2 / g, tap density Pz is 0.75 g / m 3 ; The ratio of D50 of lithium iron phosphate to the tap density of lithium iron phosphate a is 1.1, the ratio of D90 of lithium iron phosphate to D10 of lithium iron phosphate b is 5.15, and the specific surface area of ​​D50 of lithium iron phosphate to lithium iron phosphate c is 0.06.

[0131] Graphite negative electrode material: particle size D10 is 3.40 μm, D50 is 6.40 μm, D90 is 11.90 μm, D99 is 16.58 μm, specific surface area S is 1.90 m 2 / g, tap density Pz is 0.99 g / m 3 ; The ratio of graphite D50 to specific surface area d is 3.37, the ratio of graphite D50 to tap density e is 6.46, and the ratio of graphite D90 to graphite D10 f is 3.50.

[0132] (1) Preparation of positive electrode slurry: lithium iron phosphate positive electrode material, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon black Super P are uniformly mixed in a mass ratio of 96.5%: 2%: 1.5% to prepare positive electrode slurry;

[0133] (2) evenly coating the positive electrode slurry prepared in step (1) on the positive electrode current collector aluminum foil to obtain a positive electrode sheet;

[0134] (3) Negative electrode slurry: Graphite negative electrode material, binder styrene butadiene rubber SBR, binder carboxymethyl cellulose CMC, and conductive agent conductive carbon black Super P are uniformly mixed in a mass ratio of 96.8%:1.2%:0.8%:1.2% to prepare negative electrode slurry;

[0135] (4) uniformly coating the negative electrode slurry prepared in step (3) on the negative electrode current collector copper foil to obtain a negative electrode sheet;

[0136] (5) The positive electrode sheet prepared in step (2) and the negative electrode sheet prepared in step (4) are wound with a separator to obtain an electrode core, and the finished battery cell is obtained by baking, liquid injection, static soaking, chemical formation, aging, and capacity separation.

[0137] Example 2

[0138] The same as Example 1, except that the tap density Pz of the lithium iron phosphate positive electrode material is 1.17 g / m 3 ; The ratio a of D50 of lithium iron phosphate to the tap density of lithium iron phosphate is 0.7.

[0139] Example 3

[0140] The same as Example 1, except that the tap density Pz of the lithium iron phosphate positive electrode material is 0.9 g / m 3 ; The ratio a of D50 of lithium iron phosphate to the tap density of lithium iron phosphate is 0.91.

[0141] Example 4

[0142] The method is basically the same as Example 1, except that the particle size D10 of the lithium iron phosphate positive electrode material is 0.50 μm; and the ratio b of D90 of lithium iron phosphate to D10 of lithium iron phosphate is 4.

[0143] Example 5

[0144] The method is basically the same as Example 1, except that the particle size D10 of the lithium iron phosphate positive electrode material is 0.25 μm; and the ratio b of D90 of lithium iron phosphate to D10 of lithium iron phosphate is 8.

[0145] Example 6

[0146] The same as Example 1, except that the specific surface area S of the graphite negative electrode material is 0.91 m 2 / g; the ratio of D50 to specific surface area of ​​graphite is 7.

[0147] Example 7

[0148] The same as Example 1, except that the tap density Pz of the graphite negative electrode material is 2.1 g / m 3 ; The ratio of D50 to tap density of graphite is 3.

[0149] Example 8

[0150] It is basically the same as Example 1, except that the D90 of the graphite negative electrode material is 20.4 μm; and the ratio f of the D90 of graphite to the D10 of graphite is 6.

[0151] Comparative Example 1

[0152] It is basically the same as Example 1, except that:

[0153] Lithium iron phosphate cathode material: particle size D10 is 0.40 μm, D50 is 1.35 μm, D90 is 4.30 μm, D99 is 7.56 μm, and specific surface area is 12.30 m2 / g, tap density is 0.82 g / m 3 ; The ratio of D50 of lithium iron phosphate to the tap density of lithium iron phosphate a is 1.64, the ratio of D90 of lithium iron phosphate to D10 of lithium iron phosphate b is 10.75, and the specific surface area of ​​D50 of lithium iron phosphate to lithium iron phosphate c is 0.11.

[0154] Graphite negative electrode material: particle size D10 is 3.57 μm, D50 is 15.49 μm, D90 is 28.47 μm, D99 is 45.99 μm, and specific surface area is 0.7 m 2 / g, tap density is 1.32 g / m 3 ; The ratio of graphite D50 to specific surface area d is 22.12, the ratio of graphite D50 to tap density e is 11.76, and the ratio of graphite D90 to graphite D10 f is 8.55.

[0155] Comparative Example 2

[0156] The same as Example 1, except that the tap density Pz of the lithium iron phosphate positive electrode material is 1.5 g / m 3 ; The ratio a of D50 of lithium iron phosphate to the tap density of lithium iron phosphate is 0.55.

[0157] Comparative Example 3

[0158] The same as Example 1, except that the tap density Pz of the lithium iron phosphate positive electrode material is 0.63 g / m 3 ; The ratio a of D50 of lithium iron phosphate to the tap density of lithium iron phosphate is 1.3.

[0159] Comparative Example 4

[0160] The method is basically the same as Example 1, except that the particle size D10 of the lithium iron phosphate positive electrode material is 0.67 μm; and the ratio b of D90 of lithium iron phosphate to D10 of lithium iron phosphate is 3.

[0161] Comparative Example 5

[0162] It is basically the same as Example 1, except that the particle size D10 of the lithium iron phosphate positive electrode material is 0.2 μm; and the ratio b of D90 of lithium iron phosphate to D10 of lithium iron phosphate is 10.

[0163] The parameters of the positive electrode materials used in the embodiments and comparative examples are shown in Table 1.

[0164] Table 1

[0165]

[0166] The parameters of the negative electrode materials used in the embodiments and comparative examples are shown in Table 2.

[0167] Table 2

[0168]

[0169] The battery cells prepared in each embodiment and comparative example were subjected to performance tests, and the test steps were as follows:

[0170] 1. Low temperature cycle performance test:

[0171] ① Place the battery cell in a 5℃ high and low temperature oven for 6 hours;

[0172] ②0.5P charge to 3.65V;

[0173] ③ Leave it aside for 10 minutes;

[0174] ④0.5P discharge to 2.5V;

[0175] ⑤ Leave it aside for 10 minutes;

[0176] Repeat steps ②~⑤ to perform a cyclic test.

[0177] 2. Low temperature charging capability test:

[0178] ① Place the battery cell in a -10℃ high and low temperature oven for 6 hours;

[0179] ②0.5P discharge to 2.5V;

[0180] ③ Leave it aside for 10 minutes;

[0181] ④Verify charging at different rates (0.05P, 0.1P, 0.15P, 0.2P, 0.25P in increasing order) to 3.65V;

[0182] ⑤After leaving the battery at 25℃ for 120 minutes, disassemble it and observe the surface condition of the negative electrode.

[0183] The comparison of the low temperature cycle of the battery cells prepared in Example 1 and Comparative Example 1 at 5°C 0.5P / 0.5P 100% DOD is shown in the figure. Figure 1 shown.

[0184] from Figure 1 It can be seen that the battery cell prepared in Example 1 has an energy retention rate of 102% after 500 cycles at 5°C, and has not decayed; the battery cell prepared in Comparative Example 1 has an energy retention rate of 96% after 30 cycles at 5°C, and decays rapidly.

[0185] The surface condition of the negative electrode of the battery cell prepared in Example 1 after charging at 0.2P at -10°C is as follows: Figure 2 As shown, the surface of the negative electrode of the battery cell prepared in Comparative Example 1 after 0.2P charging at -10°C low temperature is as follows Figure 3 shown.

[0186] from Figure 2 It can be seen that the surface of the negative electrode of the battery cell prepared in Example 1 is golden yellow under 0.2P charging conditions at a low temperature of -10°C, and no lithium is deposited, and the battery cell has a 0.2P charging capacity under a low temperature of -10°C.

[0187] from Figure 3 It can be seen that the battery cell prepared in Comparative Example 1 has a large amount of gray lithium precipitation products on the negative electrode surface after 0.2P charging at a low temperature of -10°C, and the lithium precipitation is serious. After testing, it only has a 0.05P charging capacity at a low temperature of -10°C.

[0188] The test results of various embodiments and comparative examples are shown in Table 3.

[0189] Table 3

[0190]

[0191] As can be seen from Table 3, compared with the comparative examples, the low-temperature charging performance and low-temperature cycle performance of the battery cells prepared in each embodiment are better; among them, the -10℃ low-temperature charging capacity of the battery cells of Examples 1 to 5 is all above 0.2P, and the capacity retention rate after 300cls of 5℃ cycling is all above 100%, indicating that the low-temperature charging capacity and low-temperature cycle performance of the battery cells of Examples 1 to 5 are better. However, the battery cell of Comparative Example 1 only has a -10℃ low-temperature charging capacity of 0.05P, and serious lithium deposition occurs on the negative electrode surface when charging at -10℃ and 0.2P, showing the worst low-temperature cycle performance; and the battery cells of Comparative Examples 2 to 5 have a -10℃ low-temperature charging capacity of 0.1P, but the low-temperature cycle performance is significantly lower than that of the embodiment.

[0192] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0193] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A pole piece, characterized in that: The invention comprises a current collector and an active layer disposed on at least one side of the current collector, wherein the active layer comprises a lithium iron phosphate material, the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

2. The pole piece according to claim 1, characterized in that: The specific surface area of ​​the lithium iron phosphate material is δ m 2 / g, c=β / δ, 0.03≤c≤0.

09.

3. The pole piece according to any one of claims 1 to 2, characterized in that: The lithium iron phosphate material meets at least one of the following characteristics: (1)0.25 μm≤D10≤0.55 μm; (2)0.5 μm≤D50≤1.1 μm; (3)1.6 μm≤D90≤4 μm; (4) 4.5 μm≤D99≤8.5 μm; (5) The tap density of the lithium iron phosphate material is 0.5 g / m 3 ~1.5 g / m 3 ; (6) The specific surface area of ​​the lithium iron phosphate material is 6 m 2 / g ~30 m 2 / g.

4. A method for preparing a pole piece, characterized in that: The following steps are involved: An active layer is disposed on at least one side of the current collector, wherein the active layer comprises a lithium iron phosphate material, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

5. A slurry, characterized in that: The invention comprises a lithium iron phosphate material, a first binder and a first conductive agent, wherein the D50 of the lithium iron phosphate material is β μm, and the tap density of the lithium iron phosphate material is γ g / m 3 , a=β / γ, 0.7≤a≤1.2, the ratio of D90 of the lithium iron phosphate material to D10 of the lithium iron phosphate material is b, 4≤b≤8.

6. A lithium ion battery, characterized in that: A pole piece comprising the pole piece as described in any one of claims 1 to 3 or a pole piece made by the method for making the pole piece as described in claim 4.

7. The lithium ion battery according to claim 6, characterized in that The lithium-ion battery comprises a positive electrode and a negative electrode, wherein the electrode sheet serves as the positive electrode, the negative electrode comprises a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, the negative electrode active layer comprises graphite, the D50 of the graphite is σ μm, and the specific surface area of ​​the graphite is ω m 2 / g, d=σ / ω, 2.5≤d≤7.

5.

8. The lithium ion battery according to claim 7, characterized in that The graphite satisfies at least one of the following characteristics: (1) The tap density of the graphite is θ g / m 3 , e = σ / θ, 3 ≤ e ≤ 9; (2) The ratio of D90 of the graphite to D10 of the graphite is f, 2≤f≤6.

9. The lithium ion battery according to any one of claims 7 to 8, characterized in that The graphite satisfies at least one of the following characteristics: (1) 2 μm ≤ D10 ≤ 6 μm; (2) 4 μm≤D50≤12 μm; (3)9 μm≤D90≤16 μm; (4)14 μm≤D99≤26 μm; (5) The tap density of the graphite is 0.8 g / m 3 ~2 g / m 3 ; (6) The specific surface area of ​​the graphite is 0.8 m 2 / g ~3 m 2 / g.

10. An electrical device, characterized in that: Comprising a lithium ion battery as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Low-temperature cycle iron phosphate lithium-ion power battery and preparation method thereof

    CN107768667A

  • High-temperature cyclic lithium iron phosphate power battery and manufacturing method thereof

    CN107768727A

  • Cathode active material, method for preparing same, secondary battery, battery module, battery pack, and electric device

    CN117916912A

  • Positive active material and preparation method thereof, positive pole piece, secondary battery, battery module, battery pack and electric device

    CN118489168A

  • Positive electrode active material for nonaqueous electrolyte secondary battery

    EP3225592A1